(untitled) (Journal of Parents and Teachers, 2014)
Parents ’expectations about school and the treatment of their children often differ with respect to teachers’ expectations about their work and how to educate students. This article explains the importance of sharing education and cooperating together parents and teachers in this process of teaching and learning.